The British Orthopaedic Oncology Management audit protocol. Issue 1 (23rd October 2021) - Archer, James E; Chauhan, Govind S; Osman, Khabab; Thomson, Calum; Dewan, Varun; Nandra, Rajpal; Stevenson, Jonathan
Abstract: Metastatic bone disease (MBD) is a frequently encountered condition in trauma and orthopaedic practice, and delayed or inappropriate management may lead to worse oncological outcomes, dysfunction and reoperation. Updated guidance from the British Orthopaedic Oncology Society (BOOS) and British Orthopaedic Association (BOA), in 2015, aimed to raise awareness of such risks and to set clear standards for the provision of care in MBD patients. However, it is unclear whether these recommendations have been routinely adopted into clinical practice. BOOS and BOA aim to revise and update this guidance, and British Orthopaedic Association Standard for Trauma (BOAST) guidelines relating to MBD management are due to be published. The aim of this collaborative audit is to evaluate and benchmark current practice in the management of MBD prior to the publication of these BOAST guidelines, providing a baseline comparison for further future re-audit.